Relative abundance and species richness of spiders (Arachnida, Araneae) in forest gaps originated from oil and gas explotation at Urucu River Basin (Coari, Amazonas, Brazil) - Dias, Sidclay Calaça; Bonaldo, Alexandre Bragio (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2012)
Differences in relative abundance and species richness of spiders in artificial forest gaps with different levels of regeneration at Porto Urucu, Amazonas, Brazil, were investigated. Three complementary collecting methodologies were employed, resulting in the capture of 3.786 adult individuals, belonging to 623 species of 39 spider families. The present study accumulates the highest species number among all other published papers on spider inventories in the Neotropical Region, despite that 55% of the entire collection was composed of rare organisms. The most accurate algorithm for the present dataset, ACE, estimated a richness of 924 species. Rarefaction curves for each one of the 33 forest gaps sampled highlighted a group of forest gaps which exhibited significantly lower levels of species richness (40 to 43) and another group that exhibited significantly higher levels of species richness (98 to 100). Despite the non-significant differences in abundance and species richness among forest gaps, suggesting that the recorded species number is a direct function of the sampling intensity realized in each site. This suggests that the effective use of data on abundance and species richness of spiders in the evaluation of the regeneration levels of tropical forests depends on a much higher sampling effort than those which have been realized in structured inventories of these animals in Brazilian Amazonia.
Keywords: Environmental diversity; Structured inventory; Richness curves; Rarefaction; Amazon